Sprachverstehen mit Hörgeräten für 10 Standardaudiogramme - Dörfler, Constantin; Hocke, T.; Hast, A.; Hoppe, Ulrich (HNO, 2019)
Background: Improvement of speech perception in quiet is an important goal of hearing aid provision. In practice, results are highly variable. The aim of this study was to investigate the relationship between type and extent of hearing loss (audiogram type), maximum word recognition score, and aided speech perception. Materials and methods: Pure tone and speech audiometric data of 740 ears in 370 patients were reviewed. All subjects visited our hearing center for hearing aid evaluation between 2012 and 2017. The maximum word recognition score (WRSmax) and the monosyllabic speech recognition score with hearing aids, WRS65(HA) were analyzed for 10 different standard audiogram types. Results: The WRS65(HA) with hearing aids for different degrees of hearing loss is, within error boundaries, comparable to previous investigations and shows a difference of 10–20 percentage points to the WRSmax. This difference tends to be larger for flat and moderately sloping audiograms compared to steep-sloping audiograms. The ratio WRS65(HA)/WRSmax can be interpreted as an efficiency factor for hearing aid provision, since it relates speech recognition with hearing aids to the maximally achievable information carrying capacity of the hearing impaired. Conclusion: The expectation regarding hearing aid provision has to be adjusted according to maximum word recognition score, the derived quality measures, degree of hearing loss, and audiogram type.
CRIS-Team Scopus Importer:2019-11-26
Keywords: IEC 60118-15; Maximum word recognition score; Speech audiometry; Speech comprehensibility; Tone audiometry